1988
DOI: 10.3109/00016358809004770
|View full text |Cite
|
Sign up to set email alerts
|

The effect of controlled oral hygiene in overdenture wearers

Abstract: The effect of controlled oral hygiene was studied in 40 patients treated with immediate complete overdentures in one or both jaws. Before prosthetic treatment conservative periodontal treatment was conducted with intensive instruction and motivation in oral hygiene care. Caries and periodontal status were recorded before and 2-4 weeks (day 0), 6 months, and 12 months after prosthetic treatment. However, the patients were seen more frequently for motivation and professional tooth cleaning. The material included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
2
18
0
3
Order By: Relevance
“…In our findings overdentures had more bleeding on probing (45%) in contrast to patients with partial bridges (36·8%) and full bridges (22·1%). Other studies show also a high bleeding score with overdentures on natural teeth ( Budtz‐Jörgensen, 1991). Despite patient selection and motivation the ability of patients with regards to oral hygiene is different.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our findings overdentures had more bleeding on probing (45%) in contrast to patients with partial bridges (36·8%) and full bridges (22·1%). Other studies show also a high bleeding score with overdentures on natural teeth ( Budtz‐Jörgensen, 1991). Despite patient selection and motivation the ability of patients with regards to oral hygiene is different.…”
Section: Discussionmentioning
confidence: 90%
“…A similar effect of motivation was observed in a clinical study of patients with overdentures supported by natural teeth. Hussey & Linden (1986) and Budtz‐Jörgensen (1991) showed large individual differences in plaque‐scores in patients which were strongly related to their motivation.…”
Section: Discussionmentioning
confidence: 98%
“…Others have investigated the effect of regular professional denture and teeth cleaning on hygiene indices, body temperature, and pathogens. Improvements of hygiene indices, reduction of the number of days with pyrexia, and reduced prevalence of, for example, candida, lactobacillus, and other organisms were observed; it was also found that professional dental intervention can improve oral health indicators . Although these studies yielded promising results, there is a lack of clinical randomized controlled trials comparing the success and effectiveness of the different approaches used to improve oral hygiene; such studies could help to clarify this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients, however, were reluctant to come so often because they had no evident problems and were not used to visiting the dentist regularly. Other studies have the same disappointing results, especially in the absence of a strict maintenance protocol.1 [26][27][28] The results regarding the Dyna magnetic attachments were disappointing; most were lost or in a bad condition. "Wear" of the magnet cover often occurred, which lead to cracks and the loss of magnets.…”
Section: Discussionmentioning
confidence: 96%